ANALISIS RISIKO PERDAGANGAN BAWANG MERAH DENGAN VOLATILITAS HISTORIS DAN VALUE AT RISK - YAN ADITYA PRADANA; LENNY PUSPITA DEWI; PUTRI BALQIS AL KUBRO; SATRIYO PRIYO HANDOKO; MUHAMMAD ULUL ALBAB; FRANSISKUS FIDO EKA KURNIA NUGRAHA (E-Jurnal Matematika, 2026)
Shallots are one of Indonesia's most important horticultural commodities, however their prices are highly volatile, creating significant financial risks for farmers and traders. This study aims to quantify the price risk of shallot trading in East Java Province and Nganjuk Regency using historical volatility, Value at Risk (VaR), and Conditional Value at Risk (CVaR) based on rolling windows of 10, 20, &40 days. The log-return series were found to be non-normally distributed (Shapiro–Wilk, p<0.05) but stationary (ADF, p<0.05), supporting the use of the historical simulation approach. The results show that Nganjuk exhibits substantially higher price volatility than East Java, particularly over the 10-day rolling window. Consistent with this finding, the 95% VaR indicates that Nganjuk has a higher potential short-term loss than East Java (-0.0133 compared with-0.0065). Furthermore, CVaR provides a more conservative estimate of downside risk, indicating that the expected loss beyond the VaR threshold in Nganjuk is considerably larger than that estimated by VaR alone. These findings demonstrate that combining historical volatility, VaR, &CVaR provides a more comprehensive assessment of extreme price risk than volatility analysis alone, thereby extending the application of quantitative risk measurement to agricultural commodity trading and supporting risk management and policy decisions.